2018
DOI: 10.1016/j.htct.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Chikungunya virus in blood donors from Northern and Southeastern Brazil

Abstract: BackgroundChikungunya virus, an arbovirus that belongs to the Alphavirus genus of the Togaviridae family, causes a febrile illness accompanied by rash and arthralgia. It is estimated that during outbreaks, the prevalence of Chikungunya virus RNA in viremic blood donations varies between 0.4 and 2.1%; therefore, this virus may be transmitted by transfusion. In Brazil, Chikungunya virus has been claimed to cause extensive outbreaks, however, the seroprevalence of anti-Chikungunya virus IgG among Brazilian blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…The present report draws attention to the fact that CHIKV seems to have had a particular impact on the Fulni-ô people, the least urbanized Indigenous group in the Northeast Region of Brazil, showing more than 70% seroprevalence, in contrast to the absence of anti-CHIKV IgG in the Truká tribe. This significant and unexpected result in the Fulni-ô tribe differs from most epidemiological studies in the Americas, where estimated and found prevalence has been less than 50% [28][29][30]. To date, few studies have recorded such high prevalences.…”
Section: Discussioncontrasting
confidence: 65%
“…The present report draws attention to the fact that CHIKV seems to have had a particular impact on the Fulni-ô people, the least urbanized Indigenous group in the Northeast Region of Brazil, showing more than 70% seroprevalence, in contrast to the absence of anti-CHIKV IgG in the Truká tribe. This significant and unexpected result in the Fulni-ô tribe differs from most epidemiological studies in the Americas, where estimated and found prevalence has been less than 50% [28][29][30]. To date, few studies have recorded such high prevalences.…”
Section: Discussioncontrasting
confidence: 65%
“…6 Asymptomatic CHIK poses a substantial threat to transfusion. 8,25 The current study recorded two positive low blood donor samples by qRT-PCR without positive IgM response, presumably from the initial phase of viremia and likely to be infectious. Whole-genome sequencing attempts were unsuccessful, 26 likely due to low virus concentration.…”
mentioning
confidence: 72%
“…14 Cases of DENV transmission via blood transfusion have been documented, and CHIKV has the potential to be transmitted via this route. 15,16 Further, there is evidence for DENV-related fetal congenital defects, though sexual transmission has not been documented. 17 Recipients with positive post-transfusion serology results had their pretransfusion samples tested for virus-specific IgM and IgG by ELISA and for viral RNA by real-time PCR.…”
Section: Laboratory Testingmentioning
confidence: 99%